2018
DOI: 10.1088/1674-4926/39/3/034004
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium sulfide thin films growth by chemical bath deposition

Abstract: Cadmium sulfide (CdS) thin films have been prepared by a simple technique such as chemical bath deposition (CBD). A set of samples CdS were deposited on glass substrates by varying the bath temperature from 55 to 75 °C at fixed deposition time (25 min) in order to investigate the effect of deposition temperature on CdS films physical properties. The determination of growth activation energy suggests that at low temperature CdS film growth is governed by the release of Cd2+ ions in the solution. The structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The decrease of fi lm thickness after 80 °C was due to the dissolution of unstable nuclei adsorbed on the fi lm surface, or after reaching a certain thickness fi lm starts to peel off. A similar type of observation was also reported in literature by few investigators [2][3][4] Оригинальные статьи Original articles served that fi lm thickness was increased for bath temperature in the range, 55-75 °C and then decreased in the range of 75-85 °C whereas Hariech et al [4] reported that the thickness was increased for temperature that varied from 55 to 65 °C and then decreased when the temperature varied in the range, 65-75 °C. Fig.…”
Section: Results and Discussion Growth Mechanism Of Cds Thin Fi Lmssupporting
confidence: 74%
“…The decrease of fi lm thickness after 80 °C was due to the dissolution of unstable nuclei adsorbed on the fi lm surface, or after reaching a certain thickness fi lm starts to peel off. A similar type of observation was also reported in literature by few investigators [2][3][4] Оригинальные статьи Original articles served that fi lm thickness was increased for bath temperature in the range, 55-75 °C and then decreased in the range of 75-85 °C whereas Hariech et al [4] reported that the thickness was increased for temperature that varied from 55 to 65 °C and then decreased when the temperature varied in the range, 65-75 °C. Fig.…”
Section: Results and Discussion Growth Mechanism Of Cds Thin Fi Lmssupporting
confidence: 74%
“…FTO-coated substrates (Sigma-Aldrich, St. Louis, MI, USA) were cleaned as reported elsewhere [ 44 ]. Window n-CdS layer of 80 nm thickness was deposited on cleaned FTO substrates by the chemical bath deposition technique (CBD) at 90 °C as reported elsewhere [ 44 , 45 , 46 , 47 ]. The CBD reaction solution contains de-ionized water, cadmium acetate, ammonium acetate, and thiourea.…”
Section: Methodsmentioning
confidence: 99%
“…CBD is composed of two steps: nucleation and particle growth. In the nucleation step, the association and dissociation of molecules lead to the particle growth step . The SiO 2 substrate was modified by prepared ZnO nanorods, which were doped with AuNPs for increased sensitivity and offering a surface for the attachment of probe DNA.…”
Section: Electrochemical‐based Biosensorsmentioning
confidence: 99%
“…In the nucleation step, the association and dissociation of molecules lead to the particleg rowth step. [171] The SiO 2 substrate was modified by prepared ZnO nanorods, which were doped with AuNPs fori ncreaseds ensitivity and offering as urfacef or the attachment of probe DNA. The capacitance value of the electrode changed after immobilizationo ft he probe DNA on the electrode and hybridization of target DNA to probe DNA.…”
Section: Zno As An Electrochemicalb Iosensormentioning
confidence: 99%